ANALISIS KORELASI SCALED DISTANCE TERHADAP GETARAN TANAH PADA OPERASI PELEDAKAN BATU KAPUR PT. SEMEN BATURAJA (PERSERO) - roby cahyadi; Taufik Toha; syamsul komar (Politeknik Akamigas Palembang, 2017)
The study was conducted at the limestone mine location of PT. Semen Baturaja (Persero). Limestone mining activity is preceded by a process of destruction using drilling and blasting method. One of the effects on the environment of blasting activities that is the ground vibration. Ground vibration measurement was performed to determine the value of peak particle velocity (PPV) or peak vector sum (PVS). From the data of the ground vibration measurement for one year from May 19, 2016 until June 30, 2016, statistical analysis using linear regression method was carried out. The result of the analysis is the equation formula of correlation between PPV and scaled distance (SD) namely PVS = -0.1187 (SD) + 6.2026 with R2 = 0.7723 stating a strong correlation. Blasting trials were conducted three times, i.e. on June 23, 2016, July 28, 2016 in Block 17-18 B and July 1, 2016 in Block 10A. Experiments were performed to compare between PVS prediction and actual PVS in the field. Based on the three experiments conducted, there were no significant difference between the value of PPV predictions and the actual PPV which was 0.03 to 1.12. The standard used to measure vibration gound refers to ISO 7571: 2010. PT. Semen Baturaja also has standards of ground vibration for blasting that is a maximum of 3 mm / s. Based on relational equation between SD and PVS, vibration control was made by performing a calculation to find the value of PVS = 1 mm / s and PVS = 2 mm / s. Based on the calculation, the value of PVS = 1 mm / s was obtained in SD = 43.83 m / kg0.5, while the PVS = 2 mm / s was obtained in SD = 35.41 m / kg0.5.